2014
DOI: 10.1111/aas.12315
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nurse Anaesthetists' Non‐Technical Skills in the operating room

Abstract: A behavioural marker system, N-ANTS, for nurse anaesthetists was adapted from a behavioural marker system, ANTS, for anaesthesiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 22 publications
2
53
0
1
Order By: Relevance
“…They considered proper training and varied experience key elements. This view supports those in other studies in that there is increasing recognition of the need to train and assess nontechnical skills in the OT and not only social and cognitive capabilities but also emotional ones . and the study by Koh et al.…”
Section: Discussionsupporting
confidence: 87%
“…They considered proper training and varied experience key elements. This view supports those in other studies in that there is increasing recognition of the need to train and assess nontechnical skills in the OT and not only social and cognitive capabilities but also emotional ones . and the study by Koh et al.…”
Section: Discussionsupporting
confidence: 87%
“…Our review found several articles referring to the importance of NTS training for healthcare and patient safety (Andersen, Jensen, Lippert, & Ostergaard, 2010;Andrews, 2014;Baker, Capella, Hawkes, Gallo, & Clinic, 2011;Boet et al, 2014;Boet, Reeves, & Bould, 2015;Briggs et al, 2015;Brunckhorst et al, 2015;Burton & Ormrod, 2011;Capella et al, 2010;Clark, 2009;Cooper, Endacott, eISSN: 2357-1330 Cooper & Cant, 2014;Dieckmann, 2010;Dunn et al, 2007;Fletcher et al, 2003;Flin, O'Connor, & Crichton, 2008;Flin & Patey, 2011;Flin & Maran, 2015;Freeth et al, 2009;Gaba et al, 2001;Garbee et al, 2013;Gillman et al, 2015;Gundrosen, Solligård, & Aadahl, 2014;Gururaja, Yang, Paige, & Chauvin, 2008;Hicks, Coke, & Li, 2009;Hull et al, 2012;Irwin & Weidmann, 2015;Kiesewetter & Fischer, 2015;Kodate, Ross, Anderson, & Flin, 2012;Kohn, Corrigan, & Donaldson, 2000;Kutzin, 2010;Légaré el al., 2012;Lindamood et al, 2011;Lyk-Jensen et al, 2014;Martinou et al, 2015;Milligan, 2007;Mitchell & Flin, 2008;Nguyen, Elliott, Watson, & Dominguez, 2015;Paige et al, 2014;…”
Section: Resultsmentioning
confidence: 99%
“…NTS are the cognitive (decision-making, situation-awareness) and interpersonal (communication, teamwork, leadership) skills that underpin technical proficiency (Nguyen, Elliott, Watson, & Dominguez, 2015). These skills require training, and proved to be a necessary equation for error reduction (Flin & Maran, 2015;Gundrosen, Solligård, & Aadahl, 2014;Lyk-Jensen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations